فقہی نظریات کی جدید تفہیم: ابن عاشور کی اجتہادی بصیرت کا تجزیہ: Modern Interpretation of Jurisprudential Theories: An Analysis of Ibn Ashur’s Ijtihadi Insights - Muhammad Yaqoob; Umer Majeed; Ayesha Fatima Shezadi (International Research Journal of Arabic and Islamic Studies, 2024)
This study explores the contemporary understanding and interpretation of jurisprudential theories through the lens of Ibn Ashur's perspectives. Ibn Ashur, a prominent 20th-century Islamic scholar, is renowned for his contributions to the modern interpretation of Islamic jurisprudence, particularly through his work Al-Tahrir wa al-Tanwir. This research provides an in-depth analysis of Ibn Ashur's theories, focusing on his approach to reconciling traditional Islamic legal principles with contemporary issues. It examines how Ibn Ashur's thought addresses key aspects such as the adaptability of Shariah to modern contexts, the principles of social justice, and the application of legal maxims in contemporary settings. By reviewing Ibn Ashur's methodologies and interpretations, this study aims to elucidate how his theories contribute to the evolving understanding of Islamic law and its practical implications in today's world. The analysis highlights Ibn Ashur's impact on modern jurisprudence and his efforts to make Islamic legal thought relevant and applicable in the current era.